2013
DOI: 10.15690/vramn.v68i8.717
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Genetic Factors, Detoxication Systems and Oxidative Stress in the Pathogenesis of Endometriosis and Infertility (Review)

Abstract: The aim of this paper is to provide a systematic review of the role of the genetic factors, detoxication systems and oxidative stress in the pathogenesis of endometriosis and infertility. Endometriosis and infertility are still both the most uncommon diseases in gynecology. Many aspects of female reproductive function are strongly influenced by genetic factors, and numerous studies have attempted to identify susceptibility genes for disorders affecting female fertility such as polycystic ovary syndrome, endome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Many physiological processes can be influenced by OS, which can lead to negative effects or even cause pathological conditions in reproductive systems [ 10 13 , 141 ]. One explanation for these pathological conditions may be, at least in part, decreased scavenging capability of antioxidants, which can lead to excessive ROS production.…”
Section: Disturbance Of Redox State Under Pathological Conditions mentioning
confidence: 99%
“…Many physiological processes can be influenced by OS, which can lead to negative effects or even cause pathological conditions in reproductive systems [ 10 13 , 141 ]. One explanation for these pathological conditions may be, at least in part, decreased scavenging capability of antioxidants, which can lead to excessive ROS production.…”
Section: Disturbance Of Redox State Under Pathological Conditions mentioning
confidence: 99%
“…Two articles were excluded for not reporting exact genotypes [20, 31]. One article was excluded for being a single-arm study [32]. Finally, nine case-control studies [14, 17, 26, 27, 33–37] met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic heterogeneity is another factor that may explain the inconsistent results of previous studies on the association of smoking with ovarian reserve. N-acetyltransferase2 (NAT2) acetylator status (rapid, intermediate, or slow) has been shown to modify the association of smoking with different disease outcomes, with slow acetylators often more susceptible [19][20][21][22][23][24]. Taylor et al reported reduced fecundability among current smokers who are slow acetylators [20]; however, it remains to be established whether these effects on fecundability are modulated through a reduction in ovarian reserve.…”
Section: Introductionmentioning
confidence: 99%